2018
DOI: 10.3390/rs10071105
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Water Use Based on a Thermal and Optical Remote Sensing Model in the Mediterranean Region of Doñana

Abstract: Terrestrial evapotranspiration (ET) is a central process in the climate system, is a major component in the terrestrial water budget, and is responsible for the distribution of water and energy on land surfaces especially in arid and semiarid areas. In order to inform water management decisions especially in scarce water environments, it is important to assess ET vegetation use by differentiating irrigated socio-economic areas and natural ecosystems. The global remote sensing ET product MOD16 has proven to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
0
17
0
1
Order By: Relevance
“…The Priestley-Taylor Jet Propulsion Laboratory (PT-JPL) retrieval model has been evaluated extensively across a wide range of biomes [27,29,30], time scales [14,15,31], and environments [13,28,32]. The model used in this study is a slightly modified version of the original PT-JPL approach described in Fisher et al [27], which requires a minimum of commonly available meteorological forcing and satellite data.…”
Section: Model Description (Pt-jpl)mentioning
confidence: 99%
See 2 more Smart Citations
“…The Priestley-Taylor Jet Propulsion Laboratory (PT-JPL) retrieval model has been evaluated extensively across a wide range of biomes [27,29,30], time scales [14,15,31], and environments [13,28,32]. The model used in this study is a slightly modified version of the original PT-JPL approach described in Fisher et al [27], which requires a minimum of commonly available meteorological forcing and satellite data.…”
Section: Model Description (Pt-jpl)mentioning
confidence: 99%
“…These biophysical multipliers represent constraints for the surface wetness ( f wet ), fraction of green canopy f g , plant temperature ( f T ), plant moisture ( f M ) and soil moisture ( f SM ). Detailed information behind the specification of the biophysical multipliers, model parameters and model constants can be found in a range of previously published contributions [13,[27][28][29]32] and in Table S1.…”
Section: Model Description (Pt-jpl)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is these regions where accurate estimation may be of utmost importance to determine water use and management amongst competing sectors. Moyano et al [32] apply the PT-JPL model with dryland thermal modifications to the critical environment of the World Heritage Doñana region of Spain. They demonstrated that the remote sensing retrieval captured in situ measurements, providing confidence that the approach can be used for the ongoing management of these important ecosystems.…”
Section: Model Developments and Improvement In The Remote Sensing Of mentioning
confidence: 99%
“…Of course, advances will not be driven solely by just increasing spatial and temporal resolutions. Certainly, one of the most important aspects required to advance the development of evaporation models is our representation of the vegetation components inherent in the partitioning between soil evaporation, interception, and transpiration: an aspect that will benefit not only from resolution improvements, but also new retrieval approaches [32,33,41]. Given the array of existing sensing systems that span the visible, near-infrared, thermal, and microwave spectral ranges, efforts to utilize the varied information to better characterize land surface influences (e.g., plant form and function) are likely to provide further knowledge gains [42][43][44].…”
Section: Concluding Thoughts and Perspectivesmentioning
confidence: 99%